RECONCILIATION AS A MISSIONAL PARADIGM FOR POST-1994 SOUTH AFRICA (Acta Theologica)
The article aims to evaluate the church’s role in reconciliation as a missional paradigm and attempts to find answers from biblical and theological perspectives. It discusses the issues of church, congregations, reconciliation, the Bible and people within the post-1994 South African context. There is a need to spell out the reasons for reconciliation as a paradigm for missiology in South Africa. The article addresses theological reflection, spiritual formation and empowerment, reconciliation as the praxis of the church, and faith-based reconciliation. The development of a five-point process for conflict helps in discussing the context. In developing congregations to be communities of forgiveness; being Christocentric; living in Shalom; espousing the missional approach; being open and essential communities, as well as exploring spiritual formation and empowerment will be vital for the reconciliation process. The article attempts to show how reconciliation, as the praxis for the church in South Africa, can go a considerable way to minister and meet the need of the present-day church and community. This attempt will be further supported by the development of a faith-based people and congregation to contribute to the reconciliation process. The following research questions are posed: In a country that is statistically over 75 per cent Christian, why are life, actions, behaviour, morality and integrity so far removed from the Christian scriptural principles of the Bible, as the rule book and guidance for life? Why does or is the ecclesiastical Christian life not informing and impacting on life and experience in South Africa?